2012
DOI: 10.1158/2159-8290.cd-12-0189
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Esophageal Adenocarcinoma and Squamous Cell Carcinoma

Abstract: Esophageal cancer (EC) ranks sixth in cancer death. To explore its genetic origins, we performed exomic sequencing on 11 adenocarcinomas (EAC) and 12 squamous cell carcinomas (ESCCs) from the United States. Interestingly, inactivating mutations of NOTCH1 were identified in 21% of ESCCs but not in EACs. There was a substantial disparity in the spectrum of mutations, with more indels in ESCCs, A:T>C:G transversions in EACs, and C:G>G:C transversions in ESCCs (p<0.0001). Notably, NOTCH1 mutations were more freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
320
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 352 publications
(350 citation statements)
references
References 50 publications
27
320
2
1
Order By: Relevance
“…HNSCC and ESCC have some common risk factors and may be closely related 54, 55. Similar mutation pattern of NOTCH1 was also revealed by genomic characterization ESCCs 8. Exomic sequencing of 12 ESCCs in parallel with 12 esophageal adenocarcinomas (EAC) revealed frequent NOTCH1 mutations in 21% of ESCCs but not in EACs 8.…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnsupporting
confidence: 60%
See 3 more Smart Citations
“…HNSCC and ESCC have some common risk factors and may be closely related 54, 55. Similar mutation pattern of NOTCH1 was also revealed by genomic characterization ESCCs 8. Exomic sequencing of 12 ESCCs in parallel with 12 esophageal adenocarcinomas (EAC) revealed frequent NOTCH1 mutations in 21% of ESCCs but not in EACs 8.…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnsupporting
confidence: 60%
“…Similar mutation pattern of NOTCH1 was also revealed by genomic characterization ESCCs 8. Exomic sequencing of 12 ESCCs in parallel with 12 esophageal adenocarcinomas (EAC) revealed frequent NOTCH1 mutations in 21% of ESCCs but not in EACs 8. Notably, different NOTCH1 alternation patterns were observed in patients from different ethnical populations: NOTCH1 appears to mutate more frequently in North American ESCCs (21%) than Chinese ESCCs (2%).…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnsupporting
confidence: 56%
See 2 more Smart Citations
“…In recent years, promising information has emerged from comprehensive genomic profiling of relapsed and refractory cancers including separate evaluation of major esophageal cancers such as EAC and ESCC [21][22][23][24]. These research studies have identified potential genomic targets for patients with esophageal cancers, but comprehensive molecular testing has not been widely adopted in routine clinical practice for esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%